Implementasi Problem-Based Learning di Perguruan Tinggi - Sri Raharso (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
The focus of the study is to examine the effectiveness of Problem Based Learning (PBL) in the teaching learning process as compared to the conventional learning. Two classes of students taking Office Management course were involved, one being taught using PBL and the other using the conventional method. Two essay tests were given to the two classes, one given at the beginning of the semester and the other after four-week PBL program. The result of t-test indicates that PBL class performed significantly better, implying that PBL could better improve students' achievement in Office Management Course.